Pengaruh Komodifikasi dalam Penciptaan Tari pada Sanggar-Sanggar di Kota Medan - Nurlita Devayani (Universitas Negeri Medan, 2016)
Based on the enthusiasm of received the profit as much as possible causeda symptom of commodification appear in every sector of life. Included arts sector,in this case was more spesification in dance arts. Theory that used in this researchwas the theory of commodification that incuded production, distribution, andconsument. Composing theory based on the exploration, improvisation, formation,and development theory in this case was seen based on qualitative andquantitative. The time when the research conducted was in october until november2015. The place of the research conducted was on Sanggar Ai-ai Dancer atkecamatan Medan Denai and SanggarNusindo at Kecamatan Medan timur.Commodification affect the quality and quantity of dance movement andalso dance performance from Sanggar Ai-ai Dancer and Nusindo. That’s allbecause of the market demands were influenced in the process of dancecomposing, In result they gave priority to the commercial demands. Then tochange the merits became the material, occured the process of production,distribution, and consument to both of the Sanggar.